2004
DOI: 10.1051/0004-6361:20034314
|View full text |Cite
|
Sign up to set email alerts
|

First detection of cold dust in the northern shell of NGC 5128 (Centaurus A)

Abstract: Abstract. Deep far-infrared (FIR) imaging data obtained with ISOPHOT at 90 µm, 150 µm, and 200 µm detected the thermal emission from cold dust in the northern shell region of NGC 5128 (Centaurus A), where previously neutral hydrogen and molecular gas has been found. A somewhat extended FIR emission region is present in both the 150 µm and 200 µm map, while only an upper flux limit could be derived from the 90 µm data. The FIR spectral energy distribution can be reconciled with a modified blackbody spectrum wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 51 publications
5
25
0
Order By: Relevance
“…This material could remain outside the areas of the galaxies and would have low temperature (see Xilouris et al 2006). Such a case has been detected in the nearby giant elliptical galaxy Centaurus A, where ∼15 K dust has been detected outside the main body of the galaxy (see Stickel et al 2004). This was understood as a consequence of the accretion by a number of gas-rich dwarf companion galaxies that surround Centaurus A and have led to the formation of its dust lane, as well as to the filaments of atomic and molecular gas that surrounds it (see Schiminovich et al 1994;Charmandaris et al 2000).…”
Section: Cold Dust In Hickson Compact Groupsmentioning
confidence: 94%
“…This material could remain outside the areas of the galaxies and would have low temperature (see Xilouris et al 2006). Such a case has been detected in the nearby giant elliptical galaxy Centaurus A, where ∼15 K dust has been detected outside the main body of the galaxy (see Stickel et al 2004). This was understood as a consequence of the accretion by a number of gas-rich dwarf companion galaxies that surround Centaurus A and have led to the formation of its dust lane, as well as to the filaments of atomic and molecular gas that surrounds it (see Schiminovich et al 1994;Charmandaris et al 2000).…”
Section: Cold Dust In Hickson Compact Groupsmentioning
confidence: 94%
“…In addition, a temperature range 15−20 K was chosen to estimate the dust mass. As an upper limit we used the ISM cold dust temperature of our galaxies derived from the model and as a lower limit the estimated temperature of the cold dust stream ∼15 kpc from the centre of NGC5128 (Stickel et al 2004).The results are presented in the last column of Table 5. As we see, the amount of extended dust we detect near our galaxies is not enough to explain the high dust deficiencies of these systems (presented in Col. 6 of the same table).…”
Section: Diffuse Cold Dust In the Intragroup Mediummentioning
confidence: 99%
“…Another possibility is based on theory: it has been shown that it is possible for gas or dust to remain connected with the shell stars after a small merger (Kojima & Noguchi 1997;Charmandaris & Combes 2000). Observational evidence for significant amounts of dust residing in a shell was found in NGC 5128 (Stickel et al 2004). HI gas in shells has been found in M 83, NGC 2865 and NGC 3656 (Schiminovich et al 1995;Balcells et al 2001).…”
Section: Shell Coloursmentioning
confidence: 99%